International history 1871-1945 Cambridge international AS level - Wadsworth, Phil; Walsh-Atkins, Patrick (Cambridge international AS level history, 2013)
Covers the international option of the new Cambridge syllabus (code 9389). The final "Examination skills" chapter offers advice on exam technique and how to approach source investigation questions and structured essay questions.